Engineering blood outgrowth endothelial cells to optimize endothelial nitric oxide synthase and extracellular matrix production for coating of blood contacting surfaces. (June 2020) - Yuan, Yifan; Khan, Saad; Stewart, Duncan J.; Courtman, David W.
Abstract: Coverage of blood contacting surfaces by a functional endothelial layer is likely required to induce and maintain homeostasis. Blood outgrowth endothelial cells (BOECs), cultured from human peripheral blood monocytes, are readily available and functional autologous endothelial source that may represent a reasonable alternative to vascular derived cells. Endothelial nitric oxide synthase (eNOS) produces NO, an important factor that regulates homeostasis at the blood-contacting surface. We found that BOECs express markedly lower levels of eNOS protein (34% ± 13%, Western blot) and mRNA (29% ± 17%, qRT-PCR), as well as exhibiting reduced activity (49% ± 18%, Nitrite analysis) when compared to human umbilical vein endothelial cells (HUVECs) and human aortic endothelial cells. HUVECs grown on fibronectin, type I collagen, or laminin -coated surfaces exhibited significant reduction of eNOS mRNA and protein expression. However, no decrease in eNOS levels was observed in BOECs. Interestingly BOECs expressed significantly higher Collagen (Col) I compared to HUVECs, and blocking Col I synthesis significantly enhanced eNOS expression in BOECs. Inhibition of β1 integrin, focal adhesion kinase (FAK), or actin polymerization increased eNOS in both BOECs and HUVECs suggesting involvement of a signaling pathway culminating in stabilization of the cytoskeleton. Finally, we demonstrated that a Rho-associated protein kinases (ROCK) inhibitor, as a disruptor of actin stabilization, enhanced both eNOS expression and bioactivity. Taken together, our findings demonstrate that cell-ECM interactions are fundamental to the regulation of eNOS in BOECs and suggest that disruption of key intracellular pathways (such as ROCK) may be necessary to enhance functional activity of an endothelialized surface. Statement of Significance: Development of biocompatible blood-contacting biomaterial surfaces has not been possible to date, leading many investigators to believe that a complete autologous endothelial layer will be necessary. Blood outgrowth endothelial cells (BOECs), cultured from human peripheral blood monocytes, are readily available and functional autologous endothelial source. Endothelial nitric oxide synthase (eNOS) produces NO, an important factor that regulates homeostasis at the blood-contacting surface. In this study, we show that eNOS displays limited expression in cultured BOECs. We further demonstrate that a strong negative regulation of eNOS is mediated by collagen substrates and that treatment with ROCK inhibitor could enhance both eNOS expression and activity in BOECs and help to rapidly establish a functional autologous endothelial layer on cardiovascular biomaterials. Graphical abstract: Image, graphical abstract